Realisasi Anggaran Pajak Daerah Surabaya Berimplikasi pada Kesejahteraan Publik (Indo-MathEdu Intellectuals Journal, 2026)
This article aims to examine the relationship between regional tax management, good governance implementation, and taxpayer compliance levels, as influenced by nationalism. The study employed a literature study method, with data sources consisting of accredited journal articles, academic books, laws and regulations, and official government reports relevant to the research topic. The literature was selected based on its thematic relevance, source credibility, and publication recency. The data were analyzed using content analysis techniques through the stages of identification, classification, evaluation, and synthesis of findings to uncover the relationship between tax management, governance, and taxpayer compliance. The study's results indicate that the quality of public services and the application of good governance principles, such as transparency, accountability, and service effectiveness, play a significant role in increasing public trust in the government. This trust has a positive impact on taxpayer compliance. Furthermore, the study found that understanding the benefits of taxes is insufficient to encourage sustainable compliance without the internalization of nationalism. Nationalism serves as a driving factor for voluntary compliance because it fosters awareness that paying taxes is a form of contribution to national development. Therefore, the synergy between good governance, proportional regulations, and nationalism is key to improving sustainable tax compliance